2016
DOI: 10.1002/acr.22811
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Knee Instability as Risk Factors for Recurrent Falls

Abstract: Objectives Whether knee instability contributes to the increased risk of falls and fractures observed in persons with knee osteoarthritis (OA) has not been studied. We examined the association of knee buckling with the risk of falling and fall-related consequences in older adults with, or at high risk for, knee OA. Methods At the 60 month visit of the Multicenter Osteoarthritis Study, men and women ages 55 to 84 were asked about knee buckling in the past 3 months and whether they fell when a knee buckled. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 48 publications
(65 reference statements)
0
35
0
2
Order By: Relevance
“…Thus, the more recent article was retained. A total of 11 articles met the inclusion criteria, 9 records from the initial search and 2 from the updated search . Manual searching did not yield any additional records for inclusion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the more recent article was retained. A total of 11 articles met the inclusion criteria, 9 records from the initial search and 2 from the updated search . Manual searching did not yield any additional records for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Table shows the summary of characteristics of the 11 included studies, conducted across different countries. There were five cross‐sectional and six prospective study designs included in this review . The number of participants in each study varied between 30 and 684 participants for the cross‐sectional studies, and between 940 and 20 409 participants for the longitudinal cohort studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that older people with osteoarthritis of the knee have a two-fold increase in their likelihood of having a fall and those with osteoarthritis of the ankle have significantly poorer balance than those without osteoarthritis of the ankle joint [8,9]. Although the underlying mechanism is not known, it is thought that muscle weakness and altered proprioception may play a role.…”
Section: Introductionmentioning
confidence: 99%